1990
DOI: 10.1007/bf00266591
|View full text |Cite
|
Sign up to set email alerts
|

Glycoconjugate distribution in the human fundic mucosa revealed by lectin- and glycoprotein-gold cytochemistry

Abstract: The glycoconjugates of the human fundic mucosa were characterized at the ultrastructural level by means of direct (Helix pomatia agglutinin-gold complex) and indirect lectin techniques (Concanavalin A and horseradish peroxidase-gold complex; wheat germ agglutinin and ovomucoid-gold complex). Surface mucous cells and mucous neck cells secreted O-glycoproteins with N-acetylgalactosamine and N-acetylglucosamine residues at the non reducing terminus of the saccharidic chain. The secretory granules of the mucous ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…Mean particle diameter was checked by an IMCO 10 image analyzer computer (Kontron Bildanalyse; Eching, Germany) with Microm Image Processing Software (Microm; Barcelona, Spain). HPA-and UEA-I-gold complexes were prepared as reported previously (Martínez-Menárguez et al 1993: Madrid et al 1990). …”
Section: Preparation Of Lectin-gold Complexesmentioning
confidence: 99%
See 3 more Smart Citations
“…Mean particle diameter was checked by an IMCO 10 image analyzer computer (Kontron Bildanalyse; Eching, Germany) with Microm Image Processing Software (Microm; Barcelona, Spain). HPA-and UEA-I-gold complexes were prepared as reported previously (Martínez-Menárguez et al 1993: Madrid et al 1990). …”
Section: Preparation Of Lectin-gold Complexesmentioning
confidence: 99%
“…Histochemical staining with HRP-labeled lectins (WGA, HPA, UEA-I, and LTA) was performed as reported previously (Madrid et al 1989(Madrid et al ,1990. AAA-DIGlabeled lectin was also used according to Sata et al (1990) and Martínez-Menárguez et al (1993).…”
Section: Cytochemical Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the mucous neck cells are the precursors of chief cells, and that they are converted to chief cells via intermediate cells, which have characteristics of both mucous neck cells and chief cells (Townsend, 1961;Hunt and Hunt, 1962;Helander, 1969;Hattori and Fujita, 1976;Tamura and Fujita, 1983;Suzuki et al 1983;Cornaggia et al 1986; Ihida et al 1988; Kantani and Kataoka, 1989;Madrid et al 1990) In general, mucous neck cells are considered histochemically to be cells that stain positively for the PAS reaction, the GSA II reaction and upon paradox staining by Con A (Sheahan and Jervis, 1976;Wattel and Geuze, 1977;Katsuyama and Spicer, 1978;Ihida et al 1988). We reported that two types of mucous neck cell [containing alcian blue (pH 2.5) positive acidic mucin or containing hematoxylin (pH 6) positive neutral mucin (Akita et al 1985)1 can be observed in the region close to the cardia (Kaneko et al 1987).…”
mentioning
confidence: 99%